2015
DOI: 10.1016/j.freeradbiomed.2015.03.021
|View full text |Cite
|
Sign up to set email alerts
|

Sod1 gene ablation in adult mice leads to physiological changes at the neuromuscular junction similar to changes that occur in old wild-type mice

Abstract: Reactive oxygen species (ROS) are believed to be important mediators of muscle atrophy and weakness in aging and many degenerative conditions. However, the mechanisms and physiological processes specifically affected by elevated ROS in neuromuscular units that contribute to muscle weakness during aging are not well defined. Here we investigate the effects of chronic oxidative stress on neurotransmission and excitation-contraction (EC) coupling mechanisms in the levator auris longus (LAL) muscle from young (4–8… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 29 publications
(26 citation statements)
references
References 47 publications
1
25
0
Order By: Relevance
“…Moreover, although indistinguishable from WT mice at birth, by 5–8 months of age, SOD1 −/− mice show an accelerated neuromuscular ageing phenotype associated with myofibre atrophy (Figure 5), neurological impairments (Figure 6) and functional deficits 275. The features of the SOD1 −/− mouse model mimic those observed in 30 month old WT mice27, 277 and in older humans 6, 277.…”
Section: Non‐enzymatic Key Antioxidants That Contribute To the Maintementioning
confidence: 79%
See 1 more Smart Citation
“…Moreover, although indistinguishable from WT mice at birth, by 5–8 months of age, SOD1 −/− mice show an accelerated neuromuscular ageing phenotype associated with myofibre atrophy (Figure 5), neurological impairments (Figure 6) and functional deficits 275. The features of the SOD1 −/− mouse model mimic those observed in 30 month old WT mice27, 277 and in older humans 6, 277.…”
Section: Non‐enzymatic Key Antioxidants That Contribute To the Maintementioning
confidence: 79%
“…Moreover, although indistinguishable from WT mice at birth, by 5-8 months of age, SOD1 À/À mice show an accelerated neuromuscular ageing phenotype associated with myofibre atrophy (Figure 5), neurological impairments ( Figure 6) and functional deficits. 275 The features of the SOD1 À/À mouse model mimic those observed in 30 month old WT mice 27,277 and in older humans. 6,277 In addition, in common with old WT mice, skeletal muscle from SOD1 À/À rodents exhibits increased levels of oxidative damage 27,[29][30][31]33,34,276,277 and a constitutive activation of redox-sensitive transcription factors 33 ; hence, it has been suggested that this knockout murine model represents a useful model for the study of chronic oxidative damage in the context of neuromuscular ageing in an effort to identify potential mechanisms and pathways that underlie sarcopenia in humans.…”
Section: Nsod1komentioning
confidence: 82%
“…Most intracellular studies of the impact of age on NMJ function have found that the amplitude of EPPs/EPCs is greater in old than in young animals (while the opposite result—a decline in EPP amplitude with age—has been referred to in passing, we are unaware that a full account of this work has ever been published). In the majority of cases, this effect is associated with an increase in QC, with quantal size remaining unchanged . One counter‐example is a study that found an unchanged EPP amplitude but a large, unexplained increase in mEPP amplitude …”
Section: Are There Age‐related Changes In Nmj Function?mentioning
confidence: 96%
“…In the majority of cases, this effect is associated with an increase in QC, with quantal size remaining unchanged . One counter‐example is a study that found an unchanged EPP amplitude but a large, unexplained increase in mEPP amplitude …”
Section: Are There Age‐related Changes In Nmj Function?mentioning
confidence: 99%
“…Muscle fiber activation. At the neuromuscular junction, ROS production was recently demonstrated to be greater in the levator auris longus muscle in old mice compared with young mice (26). Interestingly, these changes were associated with less neurotransmitter being released at the synaptic cleft, which could cause failure in the generation of an action potential by the sarcolemma.…”
Section: Ros/rns and Muscle Qualitymentioning
confidence: 99%